Improving education as key to enhancing adaptive capacity in developing countries - Wolfgang Lutz (Fondazione Eni Enrico Mattei (FEEM), 2010)
This paper summarizes new scientific evidence supporting the hypothesis that among the many factors contributing to international development, the combination of education and health stands out as a root cause on which other dimensions of development depend. Much of this recent analysis is based on new reconstructions and projections of populations by age, sex and four levels of educational attainment for more than 120 countries using the demographic method of multi-state population dynamics. It also refers to a series of systems analytical population-development-environment case studies that comprehensively assess the role of population and education factors relative to other factors in the struggle for sustainable development. The paper also claims that most concerns about the consequences of population trends are in fact concerns about human capital, and that only by adding the 'quality' dimension of education to the traditionally narrow focus on size and age structure can some of the long-standing population controversies be resolved.
Keywords: I18; I28; 330; Human Capital; Education; Health; Root cause of development; 'Quality' dimension in population analysis